MiR-128-3p - a gray eminence of the human central nervous system - Klaudia Kiel; Sylwia Katarzyna Król; Agnieszka Bronisz; Jakub Godlewski (Elsevier, 2024)
MicroRNA-128-3p (miR-128-3p) is a versatile molecule with multiple functions in the physiopathology of the human central nervous system. Perturbations of miR-128-3p, which is enriched in the brain, contribute to a plethora of neurodegenerative disorders, brain injuries, and malignancies, as this miRNA is a crucial regulator of gene expression in the brain, playing an essential role in the maintenance and function of cells stemming from neuronal lineage. However, the differential expression of miR-128-3p in pathologies underscores the importance of the balance between its high and low levels. Significantly, numerous reports pointed to miR-128-3p as one of the most depleted in glioblastoma, implying it is a critical player in the disease's pathogenesis and thus may serve as a therapeutic agent for this most aggressive form of brain tumor. In this review, we summarize the current knowledge of the diverse roles of miR-128-3p. We focus on its involvement in the neurogenesis and pathophysiology of malignant and neurodegenerative diseases. We also highlight the promising potential of miR-128-3p as an antitumor agent for the future therapy of human cancers, including glioblastoma, and as the linchpin of brain development and function, potentially leading to the development of new therapies for neurological conditions.